Ex-vivo expression of chemokine receptors on cells surrounding cutaneous nerves in patients with HIV-Associated sensory neuropathy - Mountford, Jenjira; Octaviana, F.; Estiasari, R.; Setiawan, D.; Ariyanto, I.; Lee, Silvia; Gaff, Jessica; Chew, C.; Jackaman, Connie; Kamerman, Peter; Cherry, C.; Price, Patricia (Lippincott Williams and Wilkins, 2018)
Objective: HIV-Associated sensory neuropathy (HIV-SN) remains common in HIV+ individuals receiving antiretroviral therapy (ART), even though neurotoxic antiretroviral drugs (e.g. stavudine) have been phased out of use. Accumulating evidence indicates that the neuropathy is immune-mediated. We hypothesize that chemokines produced locally in the skin promote migration of macrophages and T cells into the tissue, damaging cutaneous nerves causing HIV-SN. Design: We assessed chemokine receptor expression on infiltrating CD14 + and CD3 + cells around cutaneous nerves in standardized skin biopsies from HIV-SN+ patients (n = 5), HIV-SN-patients (n = 9) and healthy controls (n = 4). Methods: The AIDS Clinical Trials Group Brief Peripheral Neuropathy Screen was used to assess Indonesian HIV+ patients receiving ART without stavudine (case definition: bilateral presence of at least one symptom and at least one sign of neuropathy). Distal leg skin biopsies were stained to visualize chemokine receptors (CCR2, CCR5, CXCR3, CXCR4, CX3CR1), infiltrating CD3 + and CD14 + cells, and protein-gene-product 9.5 on nerves, using immunohistochemistry and 4-colour confocal microscopy. Results: Intraepidermal nerve fibre density was variable in patients without HIV-SN and generally lower in those with HIV-SN. CX3CR1 was more evident on CD14 + cells whereas CCR2, CCR5, CXCR3 and CXCR4 were more common on CD3 + cells. Expression of CX3CR1, CCR2 and CCR5 was more common in HIV-SN+ patients than those without HIV-SN. CXCR3 and CXCR4 were upregulated in all HIV+ patients, compared with healthy controls. Conclusion: Inflammatory macrophages expressing CX3CR1 and T cells expressing CCR2 and CCR5 may participate in peripheral nerve damage leading to HIV-SN in HIV+ patients treated without stavudine. Further characterization of these cells is warranted.